Hubungan antara Strategi Koping dengan Kesejahteraan Subjektif pada Perawat di Rumah Sakit Kanker Dharmais Jakarta - Nabilla Yovanca; Evanytha; Puti Febrayosi (Jurnal Ilmiah Psikologi MIND SET, 2019)
This research aimed to find the correlation between problem-focused coping and emotion-focused coping with subjective well-being among oncology nurses at the Dharmais Cancer Hospital Jakarta. The subjects in this study amounted to 204 people were oncology nurse at Dharmais Cancer Hospital Jakarta. The type of research is a correlation quantitative approach with a non-probability sampling technique which is purposive sampling. The instrument of this research used to Satisfaction with Life Scale (SWLS), Scale of Positive and Negative Experience (SPANE), and Ways of Coping Questionnaire (WCQ). The result of this research shows that problem-focused coping and subjective well-being had a positive correlation. Then, emotion-focused coping and subjective well-being had a positive correlation. The most coping strategies used among oncology nurse is problem-focused coping.